Interns’ perspectives on impacts of the COVID-19 pandemic on the medical school to residency transition - Ariel S. Winn; Matthew D. Weaver; Katherine A. O’Donnell; Jason P. Sullivan; Rebecca Robbins; Christopher P. Landrigan; Laura K. Barger (BMC Medical Education, 2021)
Abstract Background The COVID-19 pandemic resulted in disruptions to medical school training and the transition to residency for new post-graduate year 1 resident-physicians (PGY1s). Therefore, the aim of this study was to understand the perspectives of United States PGY1s regarding the impact of the pandemic on these experiences. Our secondary aims were to understand how desire to practice medicine was impacted by the pandemic and whether PGY1s felt that they were able to meaningfully contribute to the COVID-19 response as students. Method We conducted a national, cross-sectional study of PGY1s who had recently graduated from medical school in 2020. A survey was distributed to PGY1s from across specialties, in programs distributed throughout the United States. It included questions about medical school training during the pandemic, impact on graduation timing and transition to internship, concerns about caring for patients with COVID-19, desire to practice medicine, and ability to meaningfully contribute to the pandemic. Findings are presented using descriptive statistics and univariate logistic regression models. Results 1980 PGY1s consented to participate, 1463 completed the survey (74%), and 713 met criteria for this analysis. 77% of PGY1s reported that the pandemic adversely affected their connection with their medical school communities, and 58% reported that the pandemic impeded their preparation for intern year. 4% of PGY1s reported graduating medical school and practicing as an intern earlier than their expected graduation date. While the majority of PGY1s did not have a change in desire to practice medicine, PGY1s with concerns regarding personal health or medical conditions (OR 4.92 [95% CI 3.20–7.55] p < 0.0001), the health or medical conditions of others in the home (OR 4.41 [2.87–6.77], p < 0.0001]), and PGY1s with children (OR 2.37 [1.23–4.58], p < 0.0001) were more likely to report a decreased desire. Conclusions The COVID pandemic disrupted the social connectedness and educational experiences of a majority of PGY1 residents in a sample of trainees in United States training programs. Those with health concerns and children had particularly challenging experiences. As the current and subsequent classes of PGY1s affected by COVID-19 proceed in their training, ongoing attention should be focused on their training needs, competencies, and well-being.